PENGARUH SUHU PENGERINGAN TERHADAP AKTIVITAS ANTIOKSIDAN TEH HERBAL KULIT KAKAO (Theobroma cacao L.) - Kusuma, I Gusti Ngurah Sujana; Putra, I Nengah Kencana; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 1 (2019): Jurnal ITEPA, 2019)
This study aims to determine the effect of drying temperature on the antioxidant activity of cocoa peels and obtain drying temperature that can produce herbal tea of cocoa peels with the highest antioxidant activity. The experimental design used was a Completely Random Design with drying temperature treatment which consist of 4 level ie : 65ºC, 75ºC, 85ºC and 95ºC. The treatment was repeated 4 times to obtain 16 experimental units. The results showed that drying temperature had a very significant effect on moisture content, ash content, crude fiber content, juice content, total phenol, antioxidant activity, taste (scoring) and no significant effect on panelists' preference for color, aroma, taste and overall acceptance. The drying temperature of 65ºC was the best treatment that produced herbal tea with the highest antioxidant activity (IC50 456.21 ppm), water content of 11.07%, ash content 8.17%, coarse fiber content 23.89%, extract content 19.90%, total phenol 0,0626%, aroma ordinary, color ordinary, taste not bitter and ordinary, overall acceptance ordinary.